2011
DOI: 10.1227/neu.0b013e3182077396
|View full text |Cite
|
Sign up to set email alerts
|

Pallidal Deep Brain Stimulation for Primary Dystonia in Children

Abstract: Pallidal DBS is a safe and effective treatment for PGD in patients <21 years of age. The improvement appears durable. Improvement in device design should reduce hardware-related complications over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
53
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 22 publications
2
53
0
1
Order By: Relevance
“…Marks et al reported a 17% infection rate for children with dystonic CP, 23 and Haridas et al reported a 14% infection rate for children with primary dystonia. 12 Children with dystonic CP, who are severely disabled and often wheelchair bound, may have a high risk of perioperative infectious complications. The high infection rates may simply be the result of small sample sizes, but it is imperative to identify factors that make this pediatric population more susceptible and establish better infection prophylaxis protocols.…”
Section: Infectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Marks et al reported a 17% infection rate for children with dystonic CP, 23 and Haridas et al reported a 14% infection rate for children with primary dystonia. 12 Children with dystonic CP, who are severely disabled and often wheelchair bound, may have a high risk of perioperative infectious complications. The high infection rates may simply be the result of small sample sizes, but it is imperative to identify factors that make this pediatric population more susceptible and establish better infection prophylaxis protocols.…”
Section: Infectionsmentioning
confidence: 99%
“…5 The posteroventrolateral globus pallidus internus (GPi) has become a well-established target for deep brain stimulation (DBS) in both primary and secondary dystonia. 23,35 While primary dystonia has been shown to respond robustly to pallidal stimulation in both adults and children, 1,2,6,12,21,29,39 secondary dystonia, especially that related to CP, appears to be less responsive. 1,2,9,21,23,27,30 The inherent difficulty in evaluating the effect of DBS within this heterogeneous population is that the literature is sparse and fraught with case series that include incomplete data, involve the inconsistent use of dystonia rating scales that may not be sensitive to the subtleties of secondary dystonia, and consist of patients of different age groups suffering from various forms of secondary dystonia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,4,6,8,18,21 Clinical outcome is critically dependent on exact lead placement in the posterior (motor) area of the internal pallidum, 26,28 but surgical methods to achieve excellent lead placement have not been standardized. In adults, the traditional method for DBS lead implantation involves physiological localization while patients are awake.…”
mentioning
confidence: 99%
“…166 Haridas and colleagues followed with a case series of 22 patients with primary dystonia who had 94% median improvement in their functional scores with a decrease in their oral and intrathecal medications. 76 More recently, this same group published their experience with 47 DYT1 patients who received pallidal DBS over 10 years with symptom reduction to less than 20% of baseline. In addition, 61% of their patients discontinued all dystonia-related medications after surgery.…”
Section: Treatment Of Dystoniamentioning
confidence: 99%